2021
DOI: 10.3947/ic.2020.0153
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes of School Teachers on Vaccination in Greece

Abstract: Few studies have assessed attitudes and beliefs of school teachers on vaccination. Our cross-sectional questionnaire-based prospective survey aims to explore vaccination coverage and relevant knowledge of school teachers in Greece. Out of the 217 respondents, 93% believe that vaccines offer protection but only 69.7% were completely vaccinated as per adults' National Immunization Schedule. In multivariate analysis, female gender, being a parent, beliefs that vaccination should be mandatory and imposing penaltie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
1
1
0
2
Order By: Relevance
“…Not only during the COVID-19 pandemic but also before the outbreak, teachers with children were more likely to report depression, anxiety, and stress symptoms ( 6 ). However, this result also corresponds to other studies, which found that teachers who are also parents have positive attitudes toward receiving the SARS-CoV-2 vaccine ( 65 ). It’s possible that participants were worried about the COVID-19 pandemic effects on themselves or their children.…”
Section: Discussionsupporting
confidence: 90%
“…Not only during the COVID-19 pandemic but also before the outbreak, teachers with children were more likely to report depression, anxiety, and stress symptoms ( 6 ). However, this result also corresponds to other studies, which found that teachers who are also parents have positive attitudes toward receiving the SARS-CoV-2 vaccine ( 65 ). It’s possible that participants were worried about the COVID-19 pandemic effects on themselves or their children.…”
Section: Discussionsupporting
confidence: 90%
“…Tutum sorularından alınan toplam puan 0,316 0,185 (0,147-0,224) <0,001 Yunanistan'da yapılan bir çalışmada öğretmenlerin %85'i Ulusal Bağışıklama Programlarına göre aşı olmaları gerektiğine inanmasına rağmen sadece %69,7'sinin aşılandığını ve öğretmenlerin %72,5'nin birçok aşının zorunlu olması gerektiğine inandıklarını gösterdi (14). Benzer şekilde çalışmamızda öğretmenlerin %69,9'u aşı yararının yan etkilerine kıyasla çok daha fazla olduğunu düşünmekteydi ve ulusal aşılama programındaki aşıların zorunlu olarak yapılması taraftarıydı (%74,6).…”
Section: Discussionunclassified
“…Çalışmaya katılanlar arasında evli olanlar (%84,7), çocuğu olanlar (%83,0) ve ortaokulda çalışanlar (%55,5) ağırlıktaydı. Katılımcıların AGÖ'den aldıkları puanlar 6-80 arasında değişmekte olup ortalama (SD); 59,9 (14,12) ve ortanca 60 puan idi.…”
Section: Bulgularunclassified
“…There is currently limited information on the general characterization of vaccine confidence in public-school teachers, with preliminary findings indicating the overall teachers are supportive of vaccination [ 7 , 8 ], As such, there continues to be a need to measure and characterize vaccine confidence, explore how teachers perceive their role within the school-based immunization program, and identify potential for opportunities to engage teachers more in school-based immunization programs. Increasing our understanding of vaccine confidence, in relation to the role teachers play in immunization decision making, will inform potential future interventions to improve vaccine uptake.…”
Section: Introductionmentioning
confidence: 99%